Polarity difference and the presence of phytoestrogen compounds affecting estrogenic activity of Peperomia pellucida extracts - I Gusti Agung Ayu Kartika; Muhamad Insanu; Catur Riani; Kyu, Hyuck Chung; Adnyana, I Ketut (Penerbit Universiti Kebangsaan Malaysia, 2021)
Peperomia pellucida (L.) Kunth has been studied as an anti-osteoporotic agent. However, there is no report about its estrogenic activity, which is important for its anti-osteoporotic activity. Thus, the aim of this research was to study the estrogenic potency of P. pellucida extracts. The estrogenic activity of P. pellucida extracts (n-hexane, ethyl acetate, ethanol, and water extracts) was studied using E-screen assay and confirmed with a molecular docking simulations. Further, the presence of phytoestrogen compounds was identified using thin layer chromatography (TLC), TLC densitometry, and high performance liquid chromatography. The n-hexane, ethyl acetate, and ethanol extracts at a concentration of 0.1 μg mL-1 exhibited a partial agonist effect, whereas the water extract showed full agonist effect at the similar concentration. This activity was produced through a classical ligand-dependent mechanism similar to estradiol. N-hexane and ethyl acetate extracts showed antiestrogenic activity. The TLC chromatogram evidently depicted the presence of quercetin and stigmasterol in the n-hexane and ethyl acetate extracts. Apigenin and apigetrin at concentrations of 0.239±0.076 and 1.063±0.156 μg mg-1 extract, respectively, were present in the water extract. A docking study on estrogen receptors confirmed that apigetrin prefer to produce estrogenic activity, whereas the other compounds can produce both estrogenic and antiestrogenic activity. Hence, we suggest that the bioactive compounds in the water extract are flavonoids, such as apigenin and apigetrin. In summary, the water extract is recommended to be used as an estrogenic agent.